Mental Illnesses-Associated Fxr1 and Its Negative Regulator Gsk3β Are Modulators of Anxiety and Glutamatergic Neurotransmission - Khlghatyan, Jivan; Evstratova, Alesya; Chamberland, Simon; Marakhovskaia, Aleksandra; Bahremand, Arash; Toth, Katalin; Beaulieu, Jean-Martin (Frontiers in Molecular Neuroscience, 2018)
Genetic variants of the fragile X mental retardation syndrome-related protein 1 (FXR1) have been associated to mood regulation, schizophrenia, and bipolar disorders. Nonetheless, genetic association does not indicate a functional link of a given gene to neuronal activity and associated behaviors. In addition, interaction between multiple genes is often needed to sculpt complex traits such as behavior. Thus, modulation of neuronal functions by a given gene product, such as Fxr1, has to be thoroughly studied in the context of its interactions with other gene products. Glycogen synthase kinase-3 beta (GSK3β) is a shared target of several psychoactive drugs. In addition, interaction between functional polymorphisms of GSK3b and FXR1 has been implicated in mood regulation in healthy subjects and bipolar patients. However, the mechanistic underpinnings of this interaction remain unknown. We used somatic CRISPR/Cas9 mediated knockout and overexpression to investigate the impact of Fxr1 and its regulator Gsk3β on neuronal functions directly in the adult mouse brain. Suppression of Gsk3β or increase of Fxr1 expression in medial prefrontal cortex neurons leads to anxiolytic-like responses associated with a decrease in AMPA mediated excitatory postsynaptic currents. Furthermore, Fxr1 and Gsk3β modulate glutamatergic neurotransmission via regulation of AMPA receptor subunits GluA1 and GluA2 as well as vesicular glutamate transporter VGlut1. These results underscore a potential mechanism underlying the action of Fxr1 on neuronal activity and behaviors. Association between the Gsk3β-Fxr1 pathway and glutamatergic signaling also suggests how it may contribute to emotional regulation in response to mood stabilizers, or in illnesses like mood disorders and schizophrenia.